Analysis of the Effectiveness of the Employee Payroll Accounting Information System at the PTPN II Sei Semayang Central Workshop - Liza Mutia; Fauzi Arif Lubis; Laylan Syafina (International Journal on Social Science, Economics and Art, 2024)
In this study, there are still weaknesses in the supervision of recording overtime hours which can result in potential fraud in the calculation of employee working hours. This research uses qualitative research methods with data collection techniques including interviews, observation and document analysis. The results of the research Payroll Accounting Information System at PTPN II Sei Semayang central workshop are in accordance with PSAK No. 24. The payroll accounting information system is considered adequate in supporting the company's internal management.